Analyzation Transit-Oriented Development (TOD) for a railway station through geospatial analysis / Putera Muhammad Adam Mohd Fadly and Nurun Nawwarah Sulaiman - Mohd Fadly, Putera Muhammad Adam; Sulaiman, Nurun Nawwarah (Universiti Teknologi MARA (UiTM), 2024)
In these modern times, promoting sustainable land use and urban development is increasingly achieved through Transit-Oriented Development (TOD), particularly leveraging train services to enhance connectivity and reduce environmental impact. Using ArcGIS Pro, this study focuses on evaluating train stations in Putrajaya, Malaysia, to identify nearby facilities and optimize development. The project centers on Putrajaya Sentral, aiming to enhance public transportation efficiency and urban mobility while addressing critical challenges like accessibility and environmental sustainability. By creating buffer zones and analyzing spatial data, the study identifies areas suitable for TOD, emphasizing mixed-use development around transit hubs to reduce traffic congestion and improve quality of life. The research underscores the role of GIS in urban planning, aligning with global trends towards sustainable urban growth and efficient transportation networks.